Penerapan Pembelajaran Problem Based Learning (PBL) dalam Meningkatkan Kemampuan Pemecahan Masalah Siswa Kelas X M6 di SMA Negeri 5 Palu - Putri, Riska Ananta; Jamhari, Mohammad; Bialangi, Mursito S.; Shamdas, Gamar B.N.; Lilies; Febriani, Vita Indri (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to improve students’ problem-solving skills through the application of Problem-Based Learning (PBL) at SMA Negeri 5 Model Palu. This study is a classroom action research (CAR) with two cycles, each consisting of two meetings, conducted in the even semester of the 2024/2025 academic year. The research subjects were 28 students from class X M6 at SMA Negeri 5 Palu, consisting of 10 male and 18 female students. The research instruments used were student problem-solving ability tests and observation sheets of teacher and student activities. The learning tools used consisted of teaching modules using the Problem-Based Learning (PBL) model and student worksheets (LKPD). The data were analyzed based on the results of observations of teacher and student activities and problem-solving ability tests. The results showed that applying the Problem-Based Learning (PBL) model could improve students’ problem-solving abilities, with an average score of 73.04 with a percentage of 71% (incomplete) in cycle I to 87.50 with a percentage of 96% (complete) in cycle II. Applying the Problem-Based Learning (PBL) model also increased teacher teaching activities and student learning activities. Thus, the application of the Problem-Based Learning (PBL) model can improve the problem-solving skills of grade X M6 students at SMA Negeri 5 Palu.